The COVID-19, Migration and Livelihood in India: Challenges and Policy Issues: Challenges and Policy Issues - Bhagat, Ram B; R.S., Reshmi; Sahoo, Harihar; Roy, Archana K.; Govil, Dipti (Migration Letters, 2020)
The worldwide spread of COVID-19 first reported from Wuhan in China is attributed to migration and mobility of people. In this article, we present how our understanding of migration and livelihood could be helpful in designing a mitigating strategy of the economic and social impact of COVID-19 in India. We conclude that there are many challenges migrants face during the spread of COVID-19 resulting from nation-wide lockdown. Many internal migrants faced problems such as lack of food, basic amenities, lack of health care, economic stress, lack of transportation facilities to return to their native places and lack of psychological support. On the other hand, COVID-19 has also brought into sharp focus the emigrants from India and the major migration corridors India shares with the world as well. There is huge uncertainty about how long this crisis will last. This article further provides some immediate measures and long term strategies to be adopted by the government such as improving public distribution system, strengthening the public health system, integration of migrants with development, decentralisation as a strategy to provide health services, and providing support to return migrants to reintegrate them, and also strengthen the database on migration and migrant households.